Les Arméniens, les Grecs et les Juifs originaires de Grèce et de Turquie, à Paris de 1920 à 1936 - Michel Garin (Cahiers Balkaniques)
This paper gives the main lines of the book “Armenians, Greeks and Jews born in Greece and Turkey and living in Paris, 1920-1936”, published in December 2010 by the Isis editions. According to the cultural and geographical origin, five immigrant groups were distinguished: Armenians from Turkey, Greeks from Greece and Greeks from Turkey, Jews from Greece and Jews from Turkey. The paper deals first with the political and economical reasons of this heterogeneous immigration, details the main streams and their implantation in Paris, and then, describes the process of the community integration in the French society. After that, it shows how the immigration policy of the French authorities and the economical crisis restrains the access of these immigrants to the wage-earning work. Self- employed activities were developed among these immigration as alternative strategy for professional integration. Many points common to the different groups can be found as concerns the self-employed activities, as the continuous augmentation of the professional self-employment rate and the similar driving forces and development process. Nevertheless we found real differences between the groups as to self-employment rate or the wage-earning activities and the different professional activities.